A thematic analysis of UK COVID-19 vaccine hesitancy discussions on Twitter - Reeshma Jameel; Sheila Greenfield; Anna Lavis (BMC Public Health)
Abstract Background Following UK approval of the Pfizer-BioNTech and Oxford-AstraZeneca vaccines on 2/12/20 and 30/12/20 respectively, discussions about them emerged on the social media platform Twitter, (now ‘X’). Previous research has shown that Twitter/ X is used by the UK public to engage with public health announcements and that social media influences public opinions of vaccines, including COVID-19 vaccines, globally. This study explored discussions on Twitter posted in response to the UK government’s posts introducing the Pfizer-BioNTech and Oxford-AstraZeneca vaccines. The aim was to investigate vaccine hesitant views, and thereby identify barriers and facilitators to COVID-19 vaccine uptake in the UK. Methods Online ethnography was used to collect responses (‘tweet replies’) to 14 Twitter posts published by officials or departments of the UK government on the dates the Pfizer-BioNTech and Oxford-AstraZeneca vaccines received approval from the Medicines and Healthcare products Regulatory Agency (2/12/20 and 30/12/20, respectively). 16,508 responses were collected and those expressing vaccine hesitancy were analysed using reflexive thematic analysis. Results Three themes that underpinned Twitter posters’ vaccine hesitancy were identified: (1) Concerns about vaccine development and safety, (2) Information, misinformation and disinformation, (3) Distrust: Politics and ‘Big Pharma’. From these themes, eight barriers and eight facilitators to UK COVID-19 vaccine uptake were identified. Conclusion This paper highlights key obstacles to COVID-19 vaccine acceptance in the UK based on views from Twitter and contributes to the emerging literature on the relationship between social media and the public response to COVID-19 vaccines. In so doing, this analysis offers insights that are useful for the development of vaccine communication strategies more broadly, both in and beyond future pandemics, to ensure that public concerns are addressed, and misinformation and disinformation are appropriately countered.